Pemanfaatan Media Sosial Tiktok Terhadap Promosi Produk Makanan Instan - Dian Sudiantini; Teti Aliyanti; Sahira Salfaniz; Iqbal Al Baihaqi; Adam Surahman (Prisani Cendekia, 2023)
Continuous developments in the world show rapid progress in various aspects of life, such as in the current era, the use of social media has increased among the public and has created opportunities for people to do business. The use of social media in business can make it easier to market or promote their products through media available on the internet. Social media itself is a means of communication to connect sellers with consumers over unlimited distances, social media plays an important role in this era of globalization because with social media we can also develop our business anywhere and examples of social media that we can use for our business are TikTok. Another benefit of social media is helping to expand marketing targets and flexibility in promotions because it can be done anywhere and at any time and attracts public interest.